2013
DOI: 10.1007/s12600-013-0316-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytophthora infestans populations of southern Brazil in 2004 and 2005

Abstract: The populations of Phytophthora infestans (Pi) in southern Brazil in 2004 and 2005 are characterized herein. The isolates were collected from potato and tomato plants in the states of Paraná (PR), Santa Catarina (SC), and Rio Grande do Sul (RS). The mating type of 131 potato and 32 tomato isolates was determined. Forty-nine isolates from potatoes and 11 from tomatoes were analyzed for their Gpi phenotype. A subset of 35 isolates was evaluated for mitochondrial (mtDNA) polymorphisms. A sample of 146 isolates wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The disease caused by the oomycete Phytophthora infestans (Mont.) de Bary is considered the most important disease of potato crop in all producing regions worldwide ( Santana et al., 2013 ; Göre et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease caused by the oomycete Phytophthora infestans (Mont.) de Bary is considered the most important disease of potato crop in all producing regions worldwide ( Santana et al., 2013 ; Göre et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The outbreaks caused by new isolates of the late blight oomycete Phytophthora infestans (Mont.) de Bary in Europe and the Americas ( Santana et al., 2013 ; Göre et al., 2019 ; Maurice et al., 2019 ), or by the new sequevars of bacterial wilt Ralstonia solanacearum found in Brazil, Peru and Iran ( Gutarra et al., 2017 ; Santiago et al., 2017 ; Sedighian et al., 2020 ) have the potential to destroy potato fields. Lack of resistance of the current potato cultivars to the main diseases that affect the crop makes it one of the most dependent crops on agrochemical applications ( Vleeshouwers et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados de la dosis media efectiva (EC 50 ) para este fungicida concuerdan con los reportados por Lagos ( 2002) al encontrar después de evaluar 63 aislamientos procedentes del Departamento de Nariño un 24% de reacción resistente. Dentro de las razones que expliquen la ausencia de poblaciones resistentes a metalaxil en este estudio, sean los cambios presentados en el ingrediente activo, ya que desde el año 2002 se ha distribuido en el mercado variantes dos veces más efectiva que el genérico conocido como Metalaxil -M. De igual manera, el uso intensivo de esta molécula para el control del tizón tardío en la zonas productoras de papa se ha visto reducida en virtud a la aparición de productos comerciales compuestos por nuevas mezclas que contienen fungicidas de tipo preventivo y curativo como Cimoxanil, Dimetomorf, Propamocarb o Estrobulinas (Santana et al, 2013) y que resultan eficientes en el control del patógeno generando una sustitución gradual del metalaxil. Lo que indica que en general, las zonas productoras de papa en el Departamento de Nariño no generan una fuerte presión de selección y que aún se puede considerar el uso de productos a base de Metalaxil en programas de manejo que controlen este patógeno.…”
Section: Discussionunclassified
“…Reports of Arafa et al [ 61 ] identified P. infestans mating type A1 using SSR markers in Egypt with seven genotypes among fourty isolates indicating genetic variability. According to Santana et al [ 62 ], 131 potato and 32 tomato isolates were evaluated where 59 isolates were classified as A1 mating type, while 103 were A2. All the tomato isolates that were of A1 mating type presented 86/100 pattern for the enzyme GPI and mtDNA Ib, indicating that the isolates belonged to the US-1 clonal lineage.…”
Section: Morphological and Molecular Diversity Of Phytophth...mentioning
confidence: 99%